2020
DOI: 10.2337/dc18-2460
|View full text |Cite
|
Sign up to set email alerts
|

Combination Therapy With Canagliflozin Plus Liraglutide Exerts Additive Effect on Weight Loss, but Not on HbA1c, in Patients With Type 2 Diabetes

Abstract: OBJECTIVE To examine the effect of combination therapy with canagliflozin plus liraglutide on HbA 1c , endogenous glucose production (EGP), and body weight versus each therapy alone. RESEARCH DESIGN AND METHODS Forty-five patients with poorly controlled (HbA 1c 7–11%) type 2 diabetes mellitus (T2DM) on metformin with or without sulfonylurea received a 9-h measurement of EGP with [3- 3 H]glu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
52
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(58 citation statements)
references
References 21 publications
6
52
0
Order By: Relevance
“…Seven RCTs with 1913 patients were included in the systematic review and meta-analysis ( Figure 1). [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] Of these, two studies were retrieved as conference abstracts and one study was identified in ClinicalTrials.gov (NCT02964247). 25,28 Of note, for one of these conference abstracts and for the trial from ClinicalTrials.gov, we utilized post hoc data from their respective journal articles, which were published shortly after our search date.…”
Section: Search Results and Study Characteristicsmentioning
confidence: 99%
See 4 more Smart Citations
“…Seven RCTs with 1913 patients were included in the systematic review and meta-analysis ( Figure 1). [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] Of these, two studies were retrieved as conference abstracts and one study was identified in ClinicalTrials.gov (NCT02964247). 25,28 Of note, for one of these conference abstracts and for the trial from ClinicalTrials.gov, we utilized post hoc data from their respective journal articles, which were published shortly after our search date.…”
Section: Search Results and Study Characteristicsmentioning
confidence: 99%
“…25,28 Of note, for one of these conference abstracts and for the trial from ClinicalTrials.gov, we utilized post hoc data from their respective journal articles, which were published shortly after our search date. 33,36 The characteristics of included studies and participants' baseline characteristics are shown in Table 1. All studies had a parallelgroup design.…”
Section: Search Results and Study Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations